Strategi Peningkatan Kinerja Karyawan: Perspektif Iklim Organisasi, Kompensasi, dan Disiplin Kerja Melalui Kepuasan Kerja - Hafid Rezki Syahidan; Yudhistira Pradhipta Aryoko; Akhmad Darmawan; Alfalisyado (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the effect of organizational climate, compensation, and work discipline on employee performance, to explore the role of employee satisfaction and work discipline on employee performance, and the role of job satisfaction as a mediating variable. As a mediating variable. The object of this research is civil servants (PNS) at the Banyumas Regency Health Office, with a sample size of 100 respondents taken using the total sampling technique. 100 respondents were taken using the total sampling technique. This research uses a quantitative approach, where data is collected through questionnaires distributed to respondents. Through questionnaires distributed to respondents. The method used is Structural Equation Modeling (SEM) and the data processing tool used is SMART-PLS to analyze the results. The data processing tool used is SMART-PLS to analyze the relationship between variables. Research results showed that organizational climate has a positive and significant effect on employee performance, while compensation and discipline on employee performance, while compensation and work discipline do not show a significant effect. Showed no significant effect. In addition, job satisfaction was shown to function as a mediating variable that affects the relationship between compensation and employee, employee performance, and work discipline on employee performance. Implications of this study indicate that the Health Office needs to take a more holistic approach to improving employee performance by focusing on developing a positive organizational climate and increasing job satisfaction. Organizational climate and increasing job satisfaction, although compensation and work discipline remain important in the context of employee well-being.